In search of 'home' in the transnational imaginary: food, roots, and routes in memoirs by Asian Australian women writers - Ahmad, Siti Nuraishah; Ramlan, Wan Nur Madiha (The Wenshan Review, 2019)
For many people, food conveys notions and memories of home, community and identity. In a transnational world, these relations have become more pronounced as food is one the cultural goods that travel in the global networks of human migration and mobility. In diasporic and/or transnational writing, the preparation and consumption of food often appear as ways of maintaining or examining one’s ties with “home.” This paper takes the memoirs of two Asian Australian women writers, Beth Yahp’s Eat First, Talk Later (2015) and Alice Pung’s Unpolished Gem (2006), as the basis for exploring how food is deployed in the writers’ search for “home” and belonging as transnational subjects. Yahp’s memoir sets out how food and memories of eating mediate her sense of “home” as a person who is designated an Other in Malaysia and Australia. In Alice Pung’s memoirs, food acts as metaphor for her unease and anxiety as an Asian Australian growing up in a homeland that does not quite embrace her and in the shadow of another homeland that keeps her under surveillance across time and space. Using Avtar Brah’s notion of a homing desire, and concepts of authenticity and hybridity explored through food in literary and cultural studies, this paper examines the ways that the selected memoirs deploy food to interrogate the practices of inclusion and exclusion that are part of the making of a sense of “home,” and how food facilitates new ways of belonging in a transnational world.